1987
DOI: 10.1093/nar/15.5.1979
|View full text |Cite
|
Sign up to set email alerts
|

The tow classes of genes for the major potato tuber protein, patatin, are differentially expressed in tubers and roots

Abstract: The major potato tuber protein, patatin, is a family of 40kd glycoproteins that constitutes forty per cent of the soluble protein in tubers but is generally undetectable in other tissues. Fused rocket immunoelectro-phoresis was used to detect in roots patatin that is immunologically different from tuber patatin. Western blots of SDS-polyacrylamide gels show root patatin to have a different molecular weight distribution than tuber patatin isoforms, but immunoprecipitation of in vitro translation products shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 14 publications
2
51
1
Order By: Relevance
“…b Class I and class II patatins are defined by the absence or presence of a 22-bp insertion in the 59-UTR (Pikaard et al 1987).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…b Class I and class II patatins are defined by the absence or presence of a 22-bp insertion in the 59-UTR (Pikaard et al 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Pikaard et al (1987) found that two classes of patatin genes, distinguished by the presence or absence of 22 nucleotides in the 59-untranslated region (UTR), are differentially expressed Sequence data from this article have been deposited with the EMBL/ GenBank data libraries under the following accession nos. : BAC 14K07, accession no.…”
mentioning
confidence: 99%
“…Based on sequence comparison of the 5'-untranslated regions of the clones, the genes can be separated into two types, which differ by the presence (class II) or absence (class I) of a 22 nucleotide insertion just upstream of the initiation codon. Class I transcripts are tuber specific, wherease class II genes are expressed in both tubers and roots, albeit at a much lower level than class I ones [26].…”
Section: Patutinmentioning
confidence: 93%
“…In addition, patatin is also expressed in roots, albeit at a IO@fold lower level [26]. Although tuberization is always accompanied by patatin synthesis, there are several instances where its expression is observed in non-tuberizing tissues.…”
Section: Patutinmentioning
confidence: 99%
“…Patatin, as the major storage protein of potato tubers, is encoded by a gene family that can be subdivided into two classes according to structural features and expression profiles (Pikaard et al, 1987). Using a transgenic approach, it could be shown that class I genes were responsible for the high levels of patatin in developing tubers and were inducible in leaves by sucrose, whereas class II gene expression was constitutive and restricted to certain cell types of tubers and roots (K6ster-T6pfer et al, 1989;RochaSosa et al, 1989).…”
Section: Introductionmentioning
confidence: 99%